Recruitment, Development and Retention of Teacher Educators in Ethiopia: Implications for Education Quality - Wamisho, Aklilu Dalelo (Bahir Dar Journal of Education, 2022)
AbstractIt is often argued that the quality of an education system cannot exceed the quality of its teachers. One can also argue that the quality of teachers cannot exceed that of teacher educators. This gives the recruitment, development and retention of teacher educators a prominent position in any effort aimed at improvement of education quality. In Ethiopia, not much is known about the characteristics and roles of teacher educators as a distinct professional group. The study, the result of which is partly reported here, was therefore aimed at shedding some light on this area by assessing the recruitment, development and retention of teacher educators. Diverse methods have been applied to this end: document analysis, interview with deans of colleges of teacher education and a questionnaire to gather information on views of teacher educators themselves. The information gathered through review of policy documents and interview with college deans was analyzed by sorting it out thematically, the themes serving as codes. The key/first-order themes used for analysis and subsequent discussion were recruitment, development and retention of teacher educators whereas characteristics, roles and competences of teacher educators were used as second-order themes. The results indicate, among other things, that the profession of teacher educators received adequate policy attention in Ethiopia. Interviews conducted with college deans confirm that efforts have been made to recruit and develop teacher educators as per the policy provisions and requirements. There are, however, challenges that threaten to undermine efforts being made to retain capable teacher educators. These include lack of a clear career structure and commensurate salary adjustment; inadequate professional development scheme; and lack of housing facility. The paper ends by putting forward some recommendations, based on the findings.